Assessment of global sorghum production, tolerance, and climate risk - Khalifa, Muhammad; Eltahir, Elfatih A. B. (Frontiers in Sustainable Food Systems, 2023)
Some cereal crops can withstand harsh growing conditions, and, hence, can be considered an important line of defense against food shortage under climate change. Sorghum (Sorghum bicolor (L.) Monech) is the main food crop for millions of people, especially in sub-Saharan Africa and South Asia. This crop performs well under input constraints (e.g., limited water) and exhibits high resilience to adverse climate conditions (e.g., high temperature, drought, and waterlogging), making it a star crop for combating hunger under global warming. However, sorghum and other similar crops are not tolerant in absolute terms. Climate change could push the growing conditions of these crops beyond the limits they can tolerate, jeopardizing the food security of millions of people around the world. In this research, we analyzed the current status of sorghum production, trends, and factors controlling sorghum yield using empirical approaches. Especially in sub-Saharan Africa, this crop is cultivated widely under unfavorable climate conditions and sub-optimal input levels. Our findings raise multiple concerns as well as highlight opportunities for the sustainability of sorghum cultivation in a future with climate change. Sorghum yield seems to increase persistently despite global warming due to an improved inputs approach, offering hope that similar adaptation approaches can be fruitful, especially in sub-Saharan Africa. A combination of interventions including adequate use of fertilizers and technology adoption (e.g. tolerant cultivars and efficient irrigation), and better agronomic practices, is the key to boosting sorghum yield and ensuring the sustainability of this important crop under a warmer climate.